2007
DOI: 10.12702/1984-7033.v07n02a09
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity in maize inbred lines using RAPD markers

Abstract: -RAPD molecular markers were used to analyze genetic diversity between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
2
9
0
1
Order By: Relevance
“…However, the rate of polymorphisms found in the present study was similar to that observed by Bruel et al (2007) and Lanza et al (1997). Carvalho et al (2004), Moeller and Schaal (1999), and Rinaldi et al (2007) have obtained lower polymorphic indices ranging from 71 to 76%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the rate of polymorphisms found in the present study was similar to that observed by Bruel et al (2007) and Lanza et al (1997). Carvalho et al (2004), Moeller and Schaal (1999), and Rinaldi et al (2007) have obtained lower polymorphic indices ranging from 71 to 76%.…”
Section: Discussionsupporting
confidence: 90%
“…Several methods have been applied in this regard: random amplified polymorphic DNA (RAPD) (Williams et al, 1990), simple sequence repeat (SSR) (Tautz, 1989), and amplified fragment length polymorphism (AFLP) (Zabeau and Vos, 1993). RAPD is widely used in studies of maize diversity owing to its low cost and rapid detection of polymorphisms (Carvalho et al, 2004;Bruel et al, 2007). SSR features high reproducibility, accuracy, and discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Different morphological, biochemical, and molecular markers are utilized by the breeders to identify the genetic diversity among the accessions (Pejic et al, 1998;Bauer et al, 2005). However, a highly informative, cost-and time-saving technique (molecular genetic markers) has replaced all 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 other techniques (Roder et al, 1998;Carvalho et al, 2004;Bruel et al, 2007). Among these markers, SSRs have more importance because of their codominant characteristics (Pejic et al, 1998;Tautz, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…relationships among them. In the case of maize, there are a lot of papers (Osipova et al, 2003;Carvalho et al, 2004, Asif et al, 2006Bruel et al, 2007, Abuali et al, 2011, Al-Badeiry et al, 2013, Molin et al, 2013 that have reported the application of the RAPD marker technique for maize molecular identification, and the technique was proved to be effective for or verification of purity and would improve the efficiency of breeding programmes (Asif et al, 2006).…”
Section: Introductionmentioning
confidence: 99%